Cerebrospinal fluid challenges for the diagnosis of herpes simplex infection in the central nervous system - Samya Jezine DA SILVA; Mauro Jorge CABRAL-CASTRO; Maria Angélica GUIMARÃES; José Mauro PERALTA; Marzia PUCCIONI-SOHLER (Arquivos de Neuro-Psiquiatria)
Abstract Herpes simplex virus (HSV) is a cause of a severe disease of the central nervous system (CNS) in humans. The demonstration of specific antibodies in the cerebrospinal fluid (CSF) may contribute to the retrospective neurological diagnosis. However, the commercial immunological tests for HSV infection are for use in serum samples. Objective: The aim of the present study was to adapt a commercial kit anti-HSV IgG used for serum samples to be performed with a CSF sample. Methods: Forty CSF specimens from 38 patients with suspected CNS HSV infection were serially diluted for detecting anti-HSV IgG by enzyme immunoassay (EIA). The same samples were also analyzed with the polymerase chain reaction (PCR). Results: The sensitivity of EIA test for HSV was 5% (dilution 1:40) and 65% (dilution 1:2) in CSF, and HSV DNA PCR was 15%. The combined analysis of EIA (dilution 1:2) and PCR increased the sensitivity up to 72.5%. The inflammatory CSF was associated with positive HSV PCR. Conclusions: We demonstrated the importance to adapt serological anti-HSV IgG EIA test for CSF assays to increase the accuracy of the analysis, considering the low concentration of specific antibodies in CSF.